2015
DOI: 10.1007/s10965-015-0661-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of a biodegradable PEGylated copolymer from ε-caprolactone and γ-valerolactone: evaluation of reaction and functional properties

Abstract: This paper reports the chemical synthesis of methoxy poly(ethyleneglycol)-block-poly(ε-caprolactone-co-4-hydroxyvalerate) from ε-caprolactone and γ-valerolactone, a five-membered ring rarely used in chemical synthesis due to its low reactivity. This procedure enabled production of copolymers with controlled ratios of repeating units and molecular weights, as demonstrated by GPC, FT-IR and NMR characterization. Copolymer degradation rate was found to depend on macromolecular composition, and finely tuneable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Pδ-VL has a semi-crystalline structure, low melting point (~−67 °C) and glass transition temperature fluctuates between 52 and 59 °C; in addition, it exhibits less elastomeric behavior compared to PCL [7]. Pδ-VL is slightly more hydrophilic than PCL, probably due to the presence of the polar carbonyl group, and fewer ethenyl groups (one group less) in the repetitive unit of Pδ-VL compared to that of PCL [8]. The degree of biodegradability of Pδ-VL (intermediate polyester) is in between that of poly(lactic-co-glycolic acid) (PLGA) and PCL.…”
Section: Introductionmentioning
confidence: 99%
“…Pδ-VL has a semi-crystalline structure, low melting point (~−67 °C) and glass transition temperature fluctuates between 52 and 59 °C; in addition, it exhibits less elastomeric behavior compared to PCL [7]. Pδ-VL is slightly more hydrophilic than PCL, probably due to the presence of the polar carbonyl group, and fewer ethenyl groups (one group less) in the repetitive unit of Pδ-VL compared to that of PCL [8]. The degree of biodegradability of Pδ-VL (intermediate polyester) is in between that of poly(lactic-co-glycolic acid) (PLGA) and PCL.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting GBL derivative is γ -valerolactone, which brings an exocyclic methyl group. Recently, the authors reported the GVL copolymerization with ϵ -caprolactone (ECL, Fig 1 ) to give polyesters with improved hydrophilicity and hydrolytic degradation kinetics [ 16 ]. Improved functional properties derived from the presence of the substituent methyl group that significantly modified molecule arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (d,l-lactic-co-glycolic acid)(PLGA) has been widely used as a therapeutic drug delivery system in protein or polypeptide formulations due to its good biocompatibility and biodegradability [5,16,17,18,19]. This polymer consists of various ratios of lactic acid and glycolic acid [8,18,20].…”
Section: Poly(lactic-co-glycolic Acid)mentioning
confidence: 99%
“…Poly(lactide-co-glycolide) (PLGA), polyglycolic acid, polylactide (PLA), and poly(caprolactone) (PCL) are the Food and Drug Administration (FDA) approved synthetic polyesters. They are generally classified into three groups based on the polymer degradation kinetics: fast (PLGA, 1-6 months), medium (polyglycolic acid), and slow (PLA and PCL, > 12 months) [14,15,16].…”
Section: Introductionmentioning
confidence: 99%